2017
DOI: 10.1002/jum.14326
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Assessment of the Position of Fetal Conus Medullaris as a Predictor of Fetal Spinal Lesions

Abstract: We propose the combined use of CM level location and CS distance measurement for the prenatal diagnosis of fetal spinal lesions for complementary needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…For example, Perlitz et al studied the CM position of 20 to 24 weeks’ GA fetuses on 2D ultrasonography by identifying the lowest rib and counting from T12; they found that in 93% of cases, CM was located at L2, L2–3, and L3 levels. Zhao et al and Lei et al used 3‐dimensional ultrasonography to demonstrate that the normal CM was at or above L3. These results indicated that the location of the CM position relative to S1 as a reference point was similar to that of other methods.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Perlitz et al studied the CM position of 20 to 24 weeks’ GA fetuses on 2D ultrasonography by identifying the lowest rib and counting from T12; they found that in 93% of cases, CM was located at L2, L2–3, and L3 levels. Zhao et al and Lei et al used 3‐dimensional ultrasonography to demonstrate that the normal CM was at or above L3. These results indicated that the location of the CM position relative to S1 as a reference point was similar to that of other methods.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding morphology, the three studies 35 , 37 , 38 that addressed the distance between the CM and the end of the sacrum performed analyses according to gestational age group. In the studies that addressed the CM-S distance, only one 10 distributed the sample by gestational age group, while the other articles 9 , 36 , 39 , did not describe any division of the samples considering foetal age.…”
Section: Discussionmentioning
confidence: 99%
“…To identify S1, the studies evaluated lumbosacral curvature using ultrasound. This approach was performed with the use of two tangents drawn at the last lumbar and sacral ossification nuclei from bottom to top, the intersection of which was the CM 10 , 35 39 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lu et al used angled lumbosacraljoint (a 15--20° angle between L5 and S1)asa reference to assess the relative relationship between the CM and the vertebra [8] . Hopmoann etaland Zhao et al measured the distance between the CM and the end of the sacral vertebrae (conus distance, CD) and found a linear correlation between CD and gestational week, biparietal diameter, abdominal circumference and femoral length [13,14] . However, the 2D ultrasound display is limited by the fact that the time of sacral vertebra ossi cation is correlated with gestational week.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of 3D technology, the direct application of 3D reconstruction, together with using the T12 corresponding to the lowermost rib as reference, is becoming more authentic. Zhao et al compared 2D CD measurements with 3D imaging and found that 3D imaging is easierand more accurate when determining the location of foetal conus medullaris [14] . Moreover, and the application of high-frequency ultrasound showed the vertebral anatomy more clearly, giving it a signi cant advantage in the diagnosis of spinal dysraphisms.…”
Section: Discussionmentioning
confidence: 99%